Efeito in vitro do saquinavir isolado e em combinação com o itraconazol frente a cepas de histoplasma capsulatum var. capsulatum - Pereira, Juliana Fernandes (2012)
Histoplasmosis is a systemic infectious disease caused by the dimorphic fungus Histoplasma capsulatum, which has three varieties: H. capsulatum var. capsulatum, H. capsulatum var. duboisii and H. capsulatum var. farciminosum. This fungus can occur in different clinical modalities and mimic other diseases, being primarily associated with frames of immunosuppression. Despite the existence of effective therapies for the treatment of this disease, there is a need to search for new therapeutic approaches for this mycosis. Studies have shown that after the introduction of highly active antiretroviral therapy, the mortality and morbidity due to a wide variety of opportunistic infections, including mycoses, have decreased among HIV-infected patients, which may show the impact of antiretroviral therapy in these opportunistic infections. Some studies have also shown that antiretroviral drugs in the class of protease inhibitors may affect the virulence of certain fungi. Thus, this study aimed to evaluate the in vitro inhibitory effect of protease inhibitor saquinavir (SQV), alone and in combination with antifungal agents: amphotericin B (AMB), fluconazole (FLU), itraconazole (ITC), voriconazole (VRC) and caspofungin (CAS) against the H. capsulatum. It was used 30 strains of H. capsulatum in the filamentous phase and 10 strains of H. capsulatum in the yeast phase to the test of the drugs isolated. To test the combination of SAQ with ITC, 30 strains in the filamentous phase and 20 strains in the yeast phase were used. The study was conducted by broth microdilution assay, described in document M27-A2, standardized by the Clinical Laboratory Standards Institute (CLSI). The interaction of drugs was analyzed by calculating the Fractional Inhibitory Concentration Index (FICI), defined as the sum of relations between the minimum inhibitory concentration (CIM) of each drug in combination and CIM of the same drug alone, whereas values less than or equal to 0.5 suggestive synergism between the drugs. Regarding the results, SQV inhibited the growth of all strains of H. capsulatum, with CIMs ranging from 0.122 to 0.977 μg / mL for both phases. In relation to combination of SQV with antifungal agents tested, only the combination of SQV with the ITR showed synergism, with values of FICI less than 0.5, where there was a significant reduction of the CIMs of both drugs. The results suggest that SQV can act as an adjuvant therapy in vitro, increasing the inhibitory effect on fungal growth, being able to lower the CIM values of antifungal drugs. Given the above, additional studies to identify the mechanism of action of SQV against H. capsulatum are needed, as well as its interaction with the ITR antifungal.